Entrepreneurial solutions and professional training: Undertaking with the “Sueli’s Boardinghouse" - Ferreira Marques de Melo, Janaina; Queiroga Alves, Vorster; de Almeida Santos, Geovani (Guará Journal, 2019)
The "Professional Training for Microentrepreneurs" (CPMEI) outreach project developed entrepreneurial activities, aiming to assist small businesses in managing their businesses. The activities developed at Sueli Cardoso’s Boarding House are noteworthy, due to the assistance provided to overcome financial difficulties and a lack of clients. Initially, a visit was conducted, followed by a discussion group using the Brainstorming methodology (Boy, 1997), where the entire team was able to provide an "avalanche" of ideas for solving the problems encountered. The main deficiencies were in financial management and marketing of the business. The main suggestion was to prioritize the development of the restaurant and lunchbox business, aiming to maximize profits. Training was provided on financial management and social media sales strategy. The project also contributed to the development of a new logo, which was used on the storefront, the restaurant menu, flyers, and social media advertising.